Hemodynamic effects of balloon pulmonary angioplasty for the treatment of total and subtotal pulmonary artery occlusions in inoperable chronic thromboembolic pulmonary hypertension. (14th October 2021) - Stepniewski, J; Magon, W; Przybylski, R; Kopec, G
Abstract: Background: Balloon pulmonary angioplasty (BPA) has become a therapeutic option for inoperable chronic thromboembolic pulmonary hypertension (CTEH). Despite significant improvement in the technique, treatment of subtotal (STO) and total (TO) pulmonary artery occlusions with BPA may pose risk, but the efficacy is unknown. Aim: We aimed to study to assess safety and efficacy of BPA in STO/TO. Methods: We included consecutive patients with inoperable CTEPH, who underwent BPA treatment. To evaluate the efficacy and safety we grouped all BPA sessions into those in which recanalization of at least one STO or TO was performed and into those without. The primary efficacy outcome was improvement in pulmonary vascular resistance (PVR) in BPA sessions with STO/TO recanalization as compared to those without. Results: We analyzed 169 BPA sessions in 50 CTEPH patients. Out of a total number of 832 lesions subjected for BPA, 168 were classified as STOs or TOs [129 (15, 5%) and 39 (4, 7%) respectively]. Three (2, 3%) STOs and 8 (20, 5%) TOs were not recanalized despite repeated attempts. There were 90 BPA sessions with at least one STO/TO recanalization. Racanalization of at least one STO/TO was associated with a trend towards PVR improvement as compared to non-STO/TO BPAs (−69±162 vs −38±135 dyn s cm –5, p=0, 19). Recanalization of STO/TO at the level of segmental pulmonary artery as compared to subsegmental-only STO/TO recanalizations or no-STO/TO recanalization was associated with significant PVR improvement (−126±192 vs −38±135 dyn s cm –5, p=0.007). The rate of complications was similar in STO/TO and non-STO/TO BPA sessions (14.4% vs 12.6%, p=0.56). Conclusions: The use of BPA for the recanalization of subtotal and total PA occlusions is safe and effective. Recanalization of segmental STO/TOs leads to significant improvement in PVR. FUNDunding Acknowledgement: Type of funding sources: None.